Green Economy and Partnership Program in the Tofu Processing Industry: Towards Social-Economic Systems Driving Sustainable Development - Adinda Thaliya; Dania Hellin Amrina (Universitas Darussalam Gontor, 2023)
With the development of the population which continues to increase along with thetimes, there is also a shift in people's lifestyles and human desires to be able to meettheir needs, this can be seen from the many community businesses that make ends meetand encourage the family's economy without thinking about the impact on thesurrounding environment. The purpose of this study is to find out how theimplementation of the green economy and partnership program is carried out in the tofuprocessing industry in a socio-economic system to encourage sustainable development,so that later it is hoped that the results of this research resume can serve as an examplefor other processing industries to implement green economy and partnership programs.good for the socio-economic system. This research is a descriptive study using literatureand summarizing the results of previous studies. This research shows the results that thetofu processing industry on Singkep Island, Bandar Lampung City has implemented apartnership program, and through this research it can also be seen that the processingindustry studied has implemented green economy principles in promoting sustainabledevelopment. development. The existence of an exemplary application of partnershipprograms and the green economy can foster a socio-economic system that is inaccordance with the main objectives of Islamic economics, namely creating aprosperous society based on justice, equity and balance.